Β-fructosidase FosE activity in Lactobacillus paracasei regulates fructan degradation during sourdough fermentation and total FODMAP levels in steamed bread. (June 2021) - Fang, Siyi; Yan, Bowen; Tian, Fengwei; Lian, Huizhang; Zhao, Jianxin; Zhang, Hao; Chen, Wei; Fan, Daming
Abstract: Low fermentable oligo-, di- and monosaccharides, and polyols (FODMAPs) have been previously shown to effectively relieve symptoms of irritable bowel syndrome (IBS) patients. This study aimed to evaluate the effect of lactobacilli on the FODMAPs degradation during sourdough fermentation, especially on fructan. Phylogenomic analysis of lactobacilli revealed that the gene coding for β-fructosidase FosE are present in Lactobacillus paracasei . L. paracasei FJSSZ3L1 was selected to effectively degrade fructans, with a degradation percentage of 86.57 ± 2.88%. The β-fructosidase FosE activity with substrate specificity was detected in the supernatant and cell wall extract, and the location of enzyme activity was related to the growth time of the strain. Fructan content decreased during sourdough fermentation with L. paracasei . According to high-efficiency anion exchange chromatography with pulsed amperometric detection (HPAEC-PAD) analysis, the rapid hydrolyzation of higher degree of polymerization (DP) fructans resulted in a transient increase in DP 3 content after 24 h of fermentation. The fructan and FODMAPs content of steamed bread with sourdough fermented by L. paracasei FJSSZ3L1 were 0.19 ± 0.01 g/100 g and 0.31 ± 0.01 g/100 g, respectively, which are significantly lower than the critical intake standards for IBS patients. Highlights: 1.The gene coding for β-fructosidase FosE is present in L. paracasei. 2.The FosE activity was detected in the supernatant and cell wall extract. 3.The effect of FosE in L. paracasei on fructans degradation is investigated. 4. L. paracasei FJSSZ3L1 was selected to effectively degrade FODMAPs of steamed bread.